The impact of childhood maltreatment, HIV status, and their interaction on mental health outcomes and markers of systemic inflammation in women - Amanda Arnold; Heqiong Wang; C. Christina Mehta; Paula-Dene C. Nesbeth; Brahmchetna Bedi; Caitlin Kirkpatrick; Caitlin A. Moran; Abigial Powers; Alicia K. Smith; Kimbi Hagen; M. Neale Weitzmann; Ighovwerha Ofotokun; et al. (Biology of Sex Differences)
Abstract Background Childhood maltreatment and HIV are both associated with a greater risk for adverse mental health, including posttraumatic stress disorder (PTSD), depression, and increased systemic inflammation. However, it remains unknown whether childhood maltreatment and HIV interact to exacerbate PTSD, depression, and inflammation in a manner that may further increase the risk of adverse health outcomes in people living with HIV. This study investigated the interaction between childhood maltreatment and HIV status on PTSD and depression symptom severity, and on peripheral concentrations of lipopolysaccharide (LPS) and high sensitivity C-reactive protein (hsCRP) in women. We hypothesized that women living with HIV (WLWH) who report high levels of childhood maltreatment exposure would show the greatest PTSD and depressive symptoms, as well as the highest concentrations of LPS and hsCRP. Methods We conducted a cross-sectional study of 116 women (73 WLWH and 43 women without HIV). Participants completed interviews to measure trauma exposure, including childhood maltreatment, and PTSD and depression symptoms. They also provided blood samples that were analyzed for LPS and hsCRP concentrations. Results Both women living with and without HIV reported high rates of trauma exposure and showed no statistically significant differences in overall rates of childhood maltreatment. Moderate to severe childhood maltreatment was associated with higher PTSD symptom severity (p =.005), greater depression severity (p =.005), and elevated plasma LPS concentrations (p =.045), regardless of HIV status. There were no effects of childhood maltreatment on hsCRP concentrations. There were no detectable significant effects of HIV status, or interactions between HIV status and childhood maltreatment, on PTSD and depression symptoms, or LPS and hsCRP concentrations (all p’s > 0.05). Conclusions Our findings highlight the impact of childhood maltreatment on depression and PTSD symptoms and LPS concentrations in women. These results underscore the importance of trauma-informed health care in addressing childhood maltreatment to potentially improve both mental and physical health outcomes of adult women.